2014
DOI: 10.1016/j.psi.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence during pregnancy: Women's narratives about their mothering experiences

Abstract: Pregnancy Intimate partner violence Difficulties at delivery Mothering skills Qualitative research Palabras clave: Embarazo Violencia contra la mujer Dificultades durante el parto Habilidades maternales Estudio cualitativo A B S T R A C TIntimate partner violence (IPV) is a significant public health issue and the most common form of violence against women worldwide. Pregnancy does not protect against this phenomenon, which may cause adverse health outcomes for both the mother and the newborn. The main aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 71 publications
2
11
0
2
Order By: Relevance
“…In about 35% of cases, professionals at the centers described the mother's parenting practices as deficient. A recent study showed that DV can negatively affect the process of parenting (Izaguirre & Calvete, 2014), corroborating the results of the present study. These relational and parenting difficulties may be linked to the impact that an abusive environment has on all areas of a woman's life, including work, economic, and social (Helfrich et al, 2008), that result in emotional difficulties and affect the mental health of the mother and children (Levendosky & Graham-Bermann, 2001;Yoo & Huang, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In about 35% of cases, professionals at the centers described the mother's parenting practices as deficient. A recent study showed that DV can negatively affect the process of parenting (Izaguirre & Calvete, 2014), corroborating the results of the present study. These relational and parenting difficulties may be linked to the impact that an abusive environment has on all areas of a woman's life, including work, economic, and social (Helfrich et al, 2008), that result in emotional difficulties and affect the mental health of the mother and children (Levendosky & Graham-Bermann, 2001;Yoo & Huang, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…These problems can spill over into the academic area, with many boys and girls experiencing problems at school and difficulties in their social relationships (Izaguirre & Calvete, 2015). Some studies also showed that DV negatively affected the process of parenting (Izaguirre & Calvete, 2014;Levendosky & Graham-Bermann, 2001;Yoo & Huang, 2013). For example, some of the previous studies found that because of their emotional difficulties several female victims of DV displayed more negative parenting behaviors, such as greater use of spanking as a disciplinary behavior, and even abusive behaviors (Taylor, Guterman, Lee, & Rathouz, 2009).…”
Section: Impact Of Domestic Violence On Childrenmentioning
confidence: 99%
“…Violence during pregnancy is particularly harmful as it threatens both maternal and fetal life. Previous studies revealed that pregnant women who experienced violence were found to have increased risks of ante-partum hemorrhage [15], intrauterine growth retardation [16], premature rupture of membrane [17, 18], cesarean delivery [18–20], preterm birth [21, 22], low birth weight babies [17, 18, 21, 23], stillbirth [15, 23, 24], and neonatal mortality [24, 25] when compared with those who did not experience the problem.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of qualitative studies have explored different aspects of IPV with pregnant women. Although a majority were conducted in high-income countries (Bacchus, Mezey, & Bewley, 2006; Izaguirre & Calvete, 2014; Rose et al, 2010), a few studies were located in low- and middle-income countries, including South Africa. For example, Damra and colleagues (2015) explored Jordanian pregnant women’s experiences of IPV disclosure and help-seeking from health care professionals and found that lack of privacy, continuity of care, time constraints, and barriers to disclosure contributed to women’s dissatisfaction with the care they received.…”
mentioning
confidence: 99%